Ambient air pollution exposure and radiographic pulmonary vascular volumes. Issue 2 (18th April 2021) - Synn, Andrew J.; Byanova, Katerina L.; Li, Wenyuan; Gold, Diane R.; Di, Qian; Kloog, Itai; Schwartz, Joel; San José Estépar, Raúl; Washko, George R.; O'Connor, George T.; Mittleman, Murray A.; Rice, Mary B.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Exposure to higher levels of ambient air pollution is a known risk factor for cardiovascular disease but long-term effects of pollution exposure on the pulmonary vessels are unknown. Methods: Among 2428 Framingham Heart Study participants who underwent chest computed tomography (CT) between 2008 and 2011, pulmonary vascular volumes were calculated by image analysis, including the total vascular volume and small vessel volume (cross-sectional area <5 mm 2 ; BV5 defined as small vessel volume). Using spatiotemporal models and participant home address, we assigned 1-year (2008) and 5-year (2004–2008) average concentrations of fine particulate matter (PM2.5 ), elemental carbon (EC), and ground-level ozone (O3 ), and distance to major roadway. We examined associations of 1- and 5-year exposures, and distance to road, with CT vascular volumes using multivariable linear regression models. Results: There was a consistent negative association of higher O3 with lower small vessel volumes, which persisted after adjustment for distance to road. Per interquartile range (IQR) of 2008 O3, BV5 was 0.34 mL lower (95% confidence intervals [CI], −0.61 to −0.06; P = 0.02), with similar results for 5-year exposure. One-year EC exposure and closer proximity to road were weakly associated with small vessel volumes; BV5 was 0.18 mL higher per IQR of 2008 EC (95% CI, −0.05 to 0.42; P = 0.13) and 0.40 mL higher per IQR closer proximity to road (95% CI: −0.10 to 0.89; P = 0.12). PM2.5 was not associated with small vascular volumes; BV5 was 0.26 mL lower per IQR of 2008 PM2.5 (95% CI: −0.68 to 0.16; P = 0.22). Conclusions: Among community-dwelling adults living in the northeastern United States, higher exposure to O3 was associated with lower small pulmonary vessel volumes on CT.